PERAN TIM KREATIF DALAM PROSES PRODUKSI POGRAM ACARA HALO DOKTER DI TVRI DALAM MENINGKATKAN EKSISTENSI PROGRAM - Diyas Aenur Ropiq; Iin Soraya; Yogi Ariska (An Nafi': Multidisciplinary Science, 2025)
TVRI stands for Televisi Republik Indonesia, which is Indonesia’s national public broadcasting institution owned by the government. This study aims to explore and analyze the role of the creative team in the production process of the Halo Dokter program on TVRI, as well as its contribution to enhancing the program's existence amid the competitive television industry. This research uses a qualitative descriptive method with data collected through interviews, observations, and documentation. The findings show that the creative team plays a crucial role in every stage of production, including pre-production, production, and post-production. In the pre-production phase, the team is responsible for idea generation, content planning, and scriptwriting. During the production stage, they ensure that the execution of the concept aligns with the plan while maintaining visual and narrative quality. In the post-production stage, they are involved in editing and evaluation processes for continuous improvement. The active and innovative role of the creative team has proven to enhance the appeal and relevance of the Halo Dokter program in the eyes of the audience, thus increasing its existence as an informative and trusted educational program.